Glucocorticoid affects dendritic transport of BDNF-containing vesicles - Adachi, Naoki (Sci Rep, 2015)
Brain-derived neurotrophic factor (BDNF) is essential for neuronal survival, differentiation, and functions in the central nervous system (CNS). Because BDNF protein is sorted into secretory vesicles at the trans-Golgi network in the cell body after translation, transport of BDNF-containing vesicles to the secretion sites is an important process for its function. Here we examined the effect of dexamethasone (DEX), a synthetic glucocorticoid, on BDNF-containing vesicle transport and found that DEX decreased the proportion of stationary vesicles and increased velocity of the microtubule-based vesicle transport in dendrites of cortical neurons. Furthermore, DEX increased huntingtin (Htt) protein levels via glucocorticoid receptor (GR) activation, and reduction in the amount of Htt by a specific shRNA reversed the action of DEX on BDNF vesicle transport. Given that Htt protein is a positive regulator for the microtubule-dependent vesicular transport in neurons, our data suggest that glucocorticoid stimulates BDNF vesicle transport through upregulation of Htt protein levels.